2018
DOI: 10.5713/ajas.18.0070
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the knowledge of pathological processes for risk-based inspection in pig slaughterhouses (Study of 2002 to 2016)

Abstract: ObjectiveThe objective of this work was to determine the prevalence of the pathologies that caused the condemnation of pig carcasses in an area of intensive pig farming and Mediterranean climatology and to evaluate their influence in a risk-based inspection procedure for slaughterhouses.MethodsA retrospective observational investigation was carried out from 2002 to 2016 into the pathological processes that caused the condemnation of pig carcasses in a slaughterhouse from South-eastern Spain. The seasonal effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 21 publications
0
19
1
Order By: Relevance
“…On the other hand, Ghidini et al [ 10 ] and Guardone et al [ 11 ] reported erysipelas as the first cause of whole-carcass condemnation in slaughtered pigs, although, in the former study, erysipelas was diagnosed in 0.3% of the total carcasses, while, in the latter study, this percentage was even lower (0.01%). Generally, erysipelas is described as a frequent cause of total condemnation, as also shown in the other studies [ 6 ]; however, it is also known that this disease may be affected by several factors, with the environmental temperature described as a critical element for the development of the disease [ 42 ]. In fact, Sánchez et al reported an increased risk of erysipelas in autumn.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…On the other hand, Ghidini et al [ 10 ] and Guardone et al [ 11 ] reported erysipelas as the first cause of whole-carcass condemnation in slaughtered pigs, although, in the former study, erysipelas was diagnosed in 0.3% of the total carcasses, while, in the latter study, this percentage was even lower (0.01%). Generally, erysipelas is described as a frequent cause of total condemnation, as also shown in the other studies [ 6 ]; however, it is also known that this disease may be affected by several factors, with the environmental temperature described as a critical element for the development of the disease [ 42 ]. In fact, Sánchez et al reported an increased risk of erysipelas in autumn.…”
Section: Discussionmentioning
confidence: 83%
“…These activities are set before and after the stunning/death of the animals, and some of them are constituted by ante and postmortem inspections (AMI and PMI) [ 5 ]. With regard to pigs, there are a number of published studies that mainly focused on lesions derived from PMI rather than AMI at the European [ 6 , 7 , 8 , 9 ] and Italian level [ 10 , 11 , 12 ]. The data collected at the slaughterhouse during PMI are certainly of great importance because they may be indicatives of some diseases or of not optimal welfare [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The disease has also been reported with varying percentages in slaughtered pigs in Portugal [ 30 ] and Switzerland [ 56 ]. Swine erysipelas is influenced by various factors [ 57 ], among which sudden changes in environmental temperature are particularly important [ 50 , 57 ]. Although the causes of skin erythema in pig carcasses are multiple, including incorrect husbandry and/or stress, inappropriate exsanguination at slaughter, and generalized infectious disease [ 14 ], classical erysipelas cutaneous lesions are characteristic and a study conducted in the US showed that cases of suspected swine erysipelas condemned at an abattoir were always appropriately classified [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a communication failure between CA and farmers has been hypothesized by other authors in the case of a stationary trend of the main diseases over the years [ 22 ], which was observed also in this study. In Britain, it was observed that companies that paid attention to the feedback received from the slaughterhouse improved their scores over time, presumably associated with improved measures in disease management [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The safety of raw materials for the production of meat products depends on the health of slaughter livestock (Januškevičiené et al 2010). A measurable indicator of the health and hygienic condition of slaughter animals is the frequency of changes and disease conditions, as well as quality deviations found during the sanitary and veterinary examination of slaughter animals before and after slaughtering (Sánchez et al 2018). The quality of carcasses and meat depends on the technology of rearing and on the conditions of transport and ante-mortem trading of animals.…”
Section: Introductionmentioning
confidence: 99%